2020
DOI: 10.1111/jonm.12950
|View full text |Cite
|
Sign up to set email alerts
|

The working experiences of male nurses in China: Implications for male nurse recruitment and retention

Abstract: Aims To understand the working experiences and career trajectories of male nurses in China. Background Compared with developed countries, men were far more under‐represented in the nursing profession in China. Little is known about the working experiences of Chinese male nurses and the contextual factors that contribute to their low participation rate in the nursing profession. Methods In‐depth interviews with twenty‐five male nurses and two hospital administrators were conducted. All interviews were analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(112 citation statements)
references
References 21 publications
(35 reference statements)
2
101
0
1
Order By: Relevance
“…The very nature of nursing job and gender stereotypes, including heavy workload, irregular working hours, and bias from patients and the general public, are the primary factors negatively influencing male nurses' professional identity, which was in line with prior studies (Wang & Yu, 2019;Zhang et al, 2019;Zheng, 2018;Zhou, 2015). Nurses were seriously lacking in China and generally had heavy workloads (Zhang and Tu, 2020). Junior nurses in this study reported that they worked more night shifts, and experienced great stress from work, study, and life.…”
Section: Family Factors Are Less Important Practical Concerns Over Jmentioning
confidence: 70%
“…The very nature of nursing job and gender stereotypes, including heavy workload, irregular working hours, and bias from patients and the general public, are the primary factors negatively influencing male nurses' professional identity, which was in line with prior studies (Wang & Yu, 2019;Zhang et al, 2019;Zheng, 2018;Zhou, 2015). Nurses were seriously lacking in China and generally had heavy workloads (Zhang and Tu, 2020). Junior nurses in this study reported that they worked more night shifts, and experienced great stress from work, study, and life.…”
Section: Family Factors Are Less Important Practical Concerns Over Jmentioning
confidence: 70%
“…Hal ini karena adanya konsep gender yang masih melekat di masyarakat tentang profesi keperawatan sebagai pekerjaan yang cocok untuk perempuan. 22,23 Berdasarkan frekuensi penggunaan, mayoritas mahasiswa profesi ners PSIK FK-KMK UGM (82,11%) terbilang kadang -kadang (2 -3x/minggu) dalam mengakses e-learning. Hanya beberapa mahasiswa saja (2,11%) yang mengakses e-learning Made Satya Nugraha Gautama, Sugiarsih, Totok Harjanto.…”
Section: Demografiunclassified
“…According to the Spanish National Institute of Statistics [ 1 ], for the last 10 years, about 15% of Spain’s nurses have been men, and this proportion is increasing. Internationally, the figures range from 2% in China (2017) [ 2 ] and 7% in Canada (2016) [ 3 ] to 9.6% in the US (2018), 10.5% in Sweden (2016) [ 4 ], 11% in the United Kingdom (2017) [ 5 ], and 11.7% in Australia (2018) [ 6 ]. According to the World Health Organisation, in 2019 the proportion of male nurses was 14% in Europe and the Americas, 19% in Oceania, 21% in Asia and 35% in Africa [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This points out the necessity of analysing how male nurses manage the emotions linked to care and explore new non-hegemonic constructions of masculinity. Several researchers have investigated the figure of the male nurse, highlighting stereotypes and difficulties that male nurses find on the job [ 29 , 30 ] but also the advantages of incorporating men into care work [ 2 , 31 ]. Others have focused on the importance of emotion management in nursing in general [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%